COURT PRECEDENTS IN VETERANS’ CASES: HISTORICAL BACKGROUND AND CURRENT PRACTICES OF COURTS IN THE UNITED STATES - Виговський, Микола; Доценко, Віктор; Жолоб, Михайло; Федінський, Олексій (SWorldJournal, 2025)
The article examines key U.S. judicial precedents in cases concerning the legal status and social protection of military veterans, as well as the emergence of specialized Veterans Treatment Courts. Drawing on decisions of the U.S. Supreme Court and federa